A meta‐analysis identified genes responsible for distinct immune responses to trivalent inactivated and live attenuated influenza vaccines. Issue 4 (10th September 2018) - Wen, Feng; Guo, Jinyue; Huang, Shujian
Abstract: Vaccinations are the cornerstone of influenza prevention strategies. We carried out a meta‐analysis of the messenger RNA expression profiles from recipients of trivalent inactivated vaccines (TIV) or live attenuated vaccines (LAIV) to determine the different recipients' responses to these two types of vaccines, which may provide information to improve the design of future improved vaccines. We executed meta‐analysis on these datasets using a random‐effects model and identified 191 and 195 differentially expressed genes in TIV and LAIV, respectively, with an false discovery rate <0.05. The genes significantly upregulated by TIV were associated with both the innate immune response and the humoral immune response, whereas LAIV mainly activated the innate immune system. The identified genes that responsible for the immune difference between LAIV and TIV might provide new information to improve current vaccines to have better efficacy in children, adults, and the elderly. Abstract : In summary, our results indicated that processes related to innate immunity may influence the immunogenicity of both the trivalent inactivated vaccines (TIV) and live attenuated vaccines (LAIV). TIV induced the humoral immunity, whereas LAIV seemed to elicit a weaker response. These observations might explain the different efficacies of LAIV and TIV in children or adults, to some extent. The different messenger RNA expression profiles induced by LAIV and TIV might provide new information towards a solution to improve current vaccines to have better efficacy in children, adults, and elderly.